Enhancing cognitive combat readiness: Gamers’ Behaviours concentrating on convergent learning style, tacit-latent, and kinetic-active knowledge acquisitions - Sumiyana, Sumiyana; Fajri, Faridiah Aghadiati; Saputra, Muhammad Adlin; Hadi, Caraka (Frontiers in Education, 2022)
This study investigates gamers’ learning styles and knowledge acquisition behavioural patterns. It argues that gamers usually have different characteristics transforming themselves to gain distinctive competencies. In other words, this study mitigates gamers’ mechanistically distinctive attitudes and behaviours, enhancing their cognitive combat readiness, that they are on convergent learning style, tacit-latent, and kinetic-active knowledge acquisitions. Methodologically, it uses a field-experimental design using the “Clash Royale” game. Then, this research measures playing performances by average decks’ score, card collection, battle deck combinations, and the usage of gold and gems. Moreover, it collects gamer respondents using a purposive sampling method by identifying them on social media and then challenging them to play. This research finds that gamers acquire new knowledge to enhance their capabilities with convergent learning styles and familiarity with the tacit-latent and kinetic-active knowledge types. Thus, it demonstrates its attitude and behavioural validities because their inner motives construct themselves always to win the game matches genuinely. Hence, it explains that gamers generally are brilliant young individuals whose impact is to create their tactically contemporary style due to the learning cycle ending in that convergent style. Likewise, these gamers simultaneously seek flexibility to enhance the game kinetically or elastically. The authors reveal that gamers’ mental models show their learning styles and knowledge acquisition behaviours explained by their strong personalities, such as curious, workaholic, prestigious, and hedonic emotions.